Pengaruh Fasilitas Penggunaan Kereta Bandara Terhadap Kepuasan Penumpang di Bandar Udara Internasional Yogyakarta - Novita Pramayshella Pakanan; Fryda FatmayatI (MES Management Journal, 2026)
The Airport Railway of Yogyakarta International Airport (YIA) serves as a key supporting transportation mode connecting the city center with the airport. The availability of adequate facilities plays an important role in shaping passenger comfort and satisfaction (Tjiptono and Diana, 2019). This study aims to analyze the influence of airport railway facilities on passenger satisfaction at Yogyakarta International Airport. A quantitative approach was employed using a purposive sampling technique involving 100 respondents. Data were analyzed using simple linear regression, t-test, and coefficient of determination. The results indicate that airport railway facilities have a significant effect on passenger satisfaction, with a t-value of 19.335 and a coefficient of determination (R²) of 0.792.